2013
DOI: 10.4236/pst.2013.13004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effects of pain and disorders of the knee joint on knee extension strength and daily life activities in the female elderly

Abstract: This study aimed at examining the differences in leg strength and activities of daily living (ADL) ability among groups with various knee problems. The subjects consisted of 328 elderly females who were classified into three groups: those without knee pain or a knee disorder, those with knee pain, and those with a knee disorder. The subjects took a knee extension strength test and an ADL survey. Knee extension strength and ADL scores (total score and each domain score of the motions of locomotion, posture chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…It is possible that the elderly with mild unilateral pain could walk while enduring knee pain. Sugiura and Demura [15] and Sugiura et al [5] reported that laterality was found in the knee extension strength of elderly people with both mild and severe unilateral knee pain. Because a decrease in knee extension strength affects walking, it was assumed that laterality would be found in the gait of elderly people with mild and severe unilateral knee pain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible that the elderly with mild unilateral pain could walk while enduring knee pain. Sugiura and Demura [15] and Sugiura et al [5] reported that laterality was found in the knee extension strength of elderly people with both mild and severe unilateral knee pain. Because a decrease in knee extension strength affects walking, it was assumed that laterality would be found in the gait of elderly people with mild and severe unilateral knee pain.…”
Section: Discussionmentioning
confidence: 99%
“…They have difficulty in walking or standing up [5,6]. There are considerable individual differences in the degree of these conditions even among the elderly with knee joint pain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation